The Notion "Weapon" in Arabic Idioms - Torlakova, Ludmila (Journal of Arabic and Islamic Studies, 2017)
This study presents a group of Arabic idioms that have as at least one of their components a word denoting a weapon. Handling and using weapons together with exploring their potential is one of the primary experiences people have had. Thus it is worthwhile to investigate how ‘weaponry’ idioms contribute to expanding figuratively the world picture included in the realm of Arabic phraseology. Weaponry idioms are considered here within the framework of general cognitive linguistics and ‘conventional figurative language theory’ as developed by Dmitri Dobrovol’skij and Elisabeth Piirainen. An attempt is made to test whether this framework can accommodate semantic analysis of Arabic idioms containing the concept weapon. Selected phrasemes denoting situation and behavior are examined in order to look into their semantic structure and type of motivation. Since the majority of the idioms studied have been collected from dictionaries, an attempt is made to present a contemporary evaluation and assessment of their use in Modern Standard Arabic based on Internet sources.